2004
DOI: 10.1111/j.1365-2796.2004.01315.x
|View full text |Cite
|
Sign up to set email alerts
|

Undertreatment and overtreatment with statins: the Oslo Health Study 2000–2001

Abstract: Results. Of subjects with a heart attack, angina, stroke or diabetes 45% of men and 35% of women were taking a statin (P < 0.001). Of subjects with cardiovascular disease (CVD) or diabetes taking statins 61% of men and 40% of women achieved total serum cholesterol levels £5 mmol L )1 . The odds ratio for taking a statin was increased amongst subjects who also took antihypertensive drug(s) or acetylsalicylic acid, subjects with a family history of coronary heart disease (CHD) and women who had visited the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
51
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 24 publications
12
51
0
2
Order By: Relevance
“…In line with the results of Reid et al (2002) and Ramsay et al (2005), they find that the young and people with a history of myocardial infarction are those, amongst the patients with heart disease, more likely to be taking lipid-regulating drugs. Undertreatment with lipid-lowering drugs amongst older people and women has been highlighted by Tonstad et al (2004) in the Oslo Health Study and by Ma et al (2005) in the U.S. National Ambulatory Medical Care Survey. Other studies find that doctor's prescription of lipid-lowering drugs is related to the socioeconomic status (SES) of the patient (Scott et al, 1996;Ohlsson et al, 2010).…”
Section: Lipid-lowering Drugsmentioning
confidence: 98%
“…In line with the results of Reid et al (2002) and Ramsay et al (2005), they find that the young and people with a history of myocardial infarction are those, amongst the patients with heart disease, more likely to be taking lipid-regulating drugs. Undertreatment with lipid-lowering drugs amongst older people and women has been highlighted by Tonstad et al (2004) in the Oslo Health Study and by Ma et al (2005) in the U.S. National Ambulatory Medical Care Survey. Other studies find that doctor's prescription of lipid-lowering drugs is related to the socioeconomic status (SES) of the patient (Scott et al, 1996;Ohlsson et al, 2010).…”
Section: Lipid-lowering Drugsmentioning
confidence: 98%
“…In most societies men are better educated, have higher positions in society, are more financially independent and take greater control of decision making than women. Several studies have shown that men with diabetes and CVD are more likely than women with comparable conditions to receive more intensive medical treatments such as statins, antihypertensive drugs and acetylsalicylates [26,39], which would be expected to lead to better treatment outcomes. As we provided a focused, structured and personalised intervention for both men and women, quality of care could be assumed to be similar in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the prevalence of LLD use depends on the extent to which treatment-eligible individuals are treated in clinical practice. There is documented a gap between guidelines for cholesterol management and clinical practice [20,21]. Variations in treatment intensity, i.e.…”
mentioning
confidence: 99%